1987
DOI: 10.1289/ehp.877197
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of organic pollutants in aquatic species.

Abstract: Aquatic organisms can take up organic pollutants from their environment and subsequently excrete the pollutant or its biotransformation products (metabolites). Phase II (conjugation) biotransformation products are almost always less toxic than the unmetabolized organic pollutant. For many organic pollutants, the extent to which conjugates are formed is extremely important in determining the rate of excretion of the pollutant. This is because most conjugates (glycosides, sulfates, amino acid conjugates, mercapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 59 publications
4
20
0
Order By: Relevance
“…As implied by these results, the lack of association between EROD activity (P4501A level) and DNA adduct levels suggests a significant involvement of conjugating as well as DNA-repair enzymes in the regulation of DNA adduct formation and elimination, respectively, as discussed elsewhere (James, 1987;Klaunig, 1984;Zaleski et al, 1991). An increase in DNA adduct formation may require an induction threshold of P4501A that was not attained in our study (3.4-fold); thus, Monteith et al (1990) observed that an 1 I-fold preinduction in AHH activity was correlated with no more than a 1.7-fold increase in DNA-binding in a primary culture of human hepatocytes treated with radiolabelled B[a]P.…”
Section: Discussionsupporting
confidence: 52%
“…As implied by these results, the lack of association between EROD activity (P4501A level) and DNA adduct levels suggests a significant involvement of conjugating as well as DNA-repair enzymes in the regulation of DNA adduct formation and elimination, respectively, as discussed elsewhere (James, 1987;Klaunig, 1984;Zaleski et al, 1991). An increase in DNA adduct formation may require an induction threshold of P4501A that was not attained in our study (3.4-fold); thus, Monteith et al (1990) observed that an 1 I-fold preinduction in AHH activity was correlated with no more than a 1.7-fold increase in DNA-binding in a primary culture of human hepatocytes treated with radiolabelled B[a]P.…”
Section: Discussionsupporting
confidence: 52%
“…In previous studies, it has been reported that fish can conjugate xenobiotics to sulfuric acid, glucuronic acid, and glutathione (GSH; Beyer et al, 2010;James, 1987). The conjugated metabolite of PAHs in fish is primarily glucuronic acid (Bayer et al, 2010;Hornung et al, 2007), and it is known that glucuronidation of xenobiotics is performed by the action of UGT (Leaver et al, 2007).…”
Section: Pyrene Metabolites Excreted By Fishmentioning
confidence: 99%
“…Several studies on metabolism of aryl-compounds show that fish can oxidize these compounds and further transform them into glucuronide conjugates, sulfate conjugates, and mercapturic acid. Glucoside conjugates can also be formed, although these are minor conjugates in aquatic species (James, 1987;Willett et al, 2000;Luthe et al, 2002). Oxidation by cytochrome P450 (CYP) and conjugation by enzymes such as UDP-glucuronosyltransferase (UGT), sulfotransferases (SULT), and glutathione S-transferase (GST) participate in the metabolism of aryl-compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The adverse effects of toxic products on crustaceans depend on its concentration and affinity, activity (intrinsic toxicity, which is function of molecular structure) and chemical biotransformations (James, 1987) and the acclimation responses of the individual (Klerks, 1999). For biocides, such as organophosphates and carbamate anticholinesterases (antiChEs), intrinsic toxicity can be judged by measuring the inhibition of cholinesterase and propagation of action potentials on synaptic transmission (see biomarkers section).…”
Section: Toxicity and Biotransformationmentioning
confidence: 99%
“…In this phase, several enzymes introduce a polar reactive group to the molecule, making it more water soluble while also increasing the possibility of further metabolism by Phase II enzymes. Two major groups of enzymes involved in Phase I metabolism include oxidoreductases and hydrolases that are located in the endoplasmic reticulum of the cell in many organs and tissues (James, 1987 (Tang et al, 2005). Metabolites formed by conjugation reactions are usually less toxic than the unconjugated compound, although there are notable exceptions to this rule (James, 1987).…”
Section: Toxicity and Biotransformationmentioning
confidence: 99%